Indicators of Cyberbullying-Related Violence In Teenagers in Ecuador - Moreta Herrera, Carlos Rodrigo; Poveda Ríos, Santiago; Ramos Noboa, Isabel (Pensando Psicología, 2018)
Aim: To determine the presence of cyberbullying indicators in a sample of schooled adolescents in Ecuador and the most recurrent practices, as well as the existing differences by sex and type of educational institution. Materials and methods: An exploratory, comparative, descriptive study was carried out using the Cyberbullying Questionnaire (cbq) and its victimization supplement (cbq-v). Four hundred and thirty-two students in the tenth year of elementary education and third year of high school participated. Fifty-five point three percent are women and 44.7% are men, with ages between 13 and 22 (m= 15.3 years,sd= 1.13). Results: Minor virtual perpetration is 56.9%, while virtual victimization is 42.8%. Group exclusion, sending of humiliating and insulting messages, and theft of the victim’s identity were the most prevalent indicators of cyberbullying. No differences were found by sex in terms of perpetrating behavior (t = -0.18) or victimization (t = 1.12); but it is present in the prevalence of perpetrating behavior (t =-2.18) in students who come from private educational institutions. Discussion: The results of perpetration and victimization partially match those reported in other interna- tional studies, but the variations need to be explained considering other psychosocial factors.